Intimate Partner Violence and the Justice System: An Examination of the Interface - Jordan, Carol E. (2004)
Women entering the court system face a challenging experience, in part, because a courtroom can be an intimidating and difficult place for any person, and in part because women victimized by crimes in which the offender is known to them face distinctive difficulties when they seek the court’s remedies. The interface is also made more challenging for women as the literature offers disparate findings as to the efficacy of criminal justice responses and civil remedies. This article briefly explores the unique characteristics of intimate partner violence cases that influence the interface of these victims with the court system.Areviewis provided of research on the criminal justice interventions in cases of intimate partner violence; and research on the efficacy of civil protective orders